2005
DOI: 10.1038/sj.cgt.7700886
|View full text |Cite
|
Sign up to set email alerts
|

Genetic strategies for brain tumor therapy

Abstract: Gene therapy is a potentially useful approach in the treatment of human brain tumors, which are notoriously refractory to conventional approaches. Most human clinical trials to date have been unsuccessful in terms of improving patient outcome. Recent improvements in viral vectors, the development of stem cell technology, and increased understanding of the mechanism of action of therapeutic transgenes provide hope that the next generation of gene therapeutics may show increased efficacy in treatment of this dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 85 publications
0
36
0
1
Order By: Relevance
“…These therapeutic strategies have been translated into clinical trials. 3,4 Unfortunately, to date, the results achieved from most clinical trials have not shown substantial therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…These therapeutic strategies have been translated into clinical trials. 3,4 Unfortunately, to date, the results achieved from most clinical trials have not shown substantial therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that stem cells can be used as vehicles for delivering therapeutic genes to treat brain tumors (3)(4)(5). Neural stem cells exhibit extensive tropism for experimental gliomas and migrate toward outgrowing microsatellites (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The strategies of gene therapy can be categorized as follows (Mut& Ziyal,2010 Immune gene therapy aims to enhance the T cell mediated immune responce againts to brain neoplasms by using genetically modified T cell therapy, vaccination therapy and cytokine therapy (Iwami et al, 2010). Cytotoxic therapy is mainly consist of either delivering of gene or virus therapy (Aboody et al, 2008;Aghi & Chiocca, 2006;Candolfi et al, 2009;Kroeger et al, 2010;Lawler et al, 2006). The most common studied conditional cytotoxic transgene is Herpes Simplex Type 1 thymidine kinase (TK), which converts the prodrug ganciclovir (or valacyclovir) into the highly toxic deoxyguanosine triphosphate causing early chain termination of nascent DNA strands (Beltinger et al, 1999).…”
Section: Genetic and Immunology Of Brain Tumorsmentioning
confidence: 99%